Pancreatic Cancer in Canada: Incidence and Mortality Trends from 1992 to 2005 - Robert Flook; Sander Veldhuyzen van Zanten (Canadian Journal of Gastroenterology)
BACKGROUND: Pancreatic cancer is the fourth-ranking cause of death among all major malignancies in Canada and has the lowest five-year survival rate.